Influential Celebrities In Sustainable Online Shopping: A Theory Of Reasoned Action Insights - Pane, Mujahidun Hapisni; Rukiah, Rukiah; Siregar, Budi Gautama; Nasirin, Wanda Khairun; Hidayat, Randi Friscilla (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
ABSTRACTThe implementation of lockdown in 2020 as a response to COVID-19 has led to significant behavioral changes, pushing society to adapt to online transactions. This research aims to analyze the influencing factors such as e-trust, e-wom, e-servqual, and celebrity endorsers on online purchase decisions, as well as examine the moderating effect of celebrity endorsers on these decisions. The research methodology used is quantitative with stratified sampling techniques, employing the Structural Equation Model Partial Least Square (SEM-PLS) with WarpPLS 8.0 software. The results of the study indicate that e-trust and e-WOM have a positive and significant impact on online purchase decisions, while e-service quality does not have a significant influence. Another finding is that celebrity endorsers can moderate e-trust, strengthen consumer trust in online transactions, and impact purchase decisions. However, celebrity endorsers are not effective in moderating e-WOM and e-service quality in online purchase decisions. In this context, e-trust, e-WOM, and celebrity endorsers play crucial roles in influencing online purchase decisions, in line with the Theory of Reasoned Action. The practical implications of this research emphasize the importance of building consumer trust in online transactions and managing the use of celebrity endorsers wisely to enhance purchase decisions. E-commerce companies and online platforms need to provide high-quality services to strengthen consumer trust. Moreover, the role of e-WOM should also be considered to influence purchase decisions and improve online service quality according to consumer expectations. The policy recommendations resulting from this research highlight the need for companies to focus on managing consumer trust and utilizing celebrity endorsers wisely to enhance sustainable online shopping.